2005
DOI: 10.1089/ten.2005.11.110
|View full text |Cite
|
Sign up to set email alerts
|

Engrafted Bone Marrow-Derived Flk-1+Mesenchymal Stem Cells Regenerate Skin Tissue

Abstract: Stem cell plasticity has created great interest because of its potential therapeutic application in degenerative or inherited diseases. Transplantation of bone marrow-derived stem cells was shown to give rise to cells of muscle, liver, nerve, endothelium, epithelium, and so on. But there are still disputes about stem cell plasticity, especially concerning the contribution of bone marrow-derived cells to skin cells. In this study, CM-DiI fluorescence-labeled Flk-(1+) bone marrow mesenchymal stem cells (bMSCs) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 34 publications
2
107
0
1
Order By: Relevance
“…Such cells may in turn release factors that operate on the host or that may differentiate into cells that directly participate in the wound healing process via release of C7 or other tissue repair proteins [39,40]. For example, both BM and CB grafts used in the clinical trial contain MSCs that are known to migrate to sites of injury including skin wounds [4,42,44,45]. There the MSCs engage in tissue healing, predominantly by secretion of paracrine factors, including appropriate extracellular matrix molecules, and by the recruitment of reparative cells from the recipient [34].…”
Section: Resultsmentioning
confidence: 99%
“…Such cells may in turn release factors that operate on the host or that may differentiate into cells that directly participate in the wound healing process via release of C7 or other tissue repair proteins [39,40]. For example, both BM and CB grafts used in the clinical trial contain MSCs that are known to migrate to sites of injury including skin wounds [4,42,44,45]. There the MSCs engage in tissue healing, predominantly by secretion of paracrine factors, including appropriate extracellular matrix molecules, and by the recruitment of reparative cells from the recipient [34].…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, many teams have provided compelling evidence indicating that bone marrow-derived cells can be converted into skin cells (31,(35)(36)(37). These studies demonstrated that not only whole bone marrow cells but also purified hematopoietic stem cells (6) and mesenchymal stem cells (31) can differentiate into skin cells.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of this study was that perfect skin regeneration was achieved with MSCs after full-thickness wounds [3]. Also, the outcomes of Deng et al were promising, with the application of MSCs in mice transplanted into other irradiated mice [2]. They reported that bMSCs can contribute to skin functional cells and regeneration.…”
Section: Introductionmentioning
confidence: 70%
“…Mesenchymal stem cells have been used in several studies, which showed that regeneration of full-thickness wounds can be enhanced by application of MSCs [1][2][3][4]. For example, Bone Marrow derived Mesenchymal Stem Cells (bMSCs) have the potential to differentiate into osteoblasts, chondrocytes, myocytes [5][6][7][8], and adipocytes [2,5,7].…”
Section: Introductionmentioning
confidence: 99%